Linear and Nonlinear Optical Properties of Natural Dyes Freestanding Films and Application in Optical Limiting - Maha A Rahma,; Emad A. Mohammed,; Haithem L Saadon, (University of Thi-Qar Journal of Science, 2020)
Natural dyes were followed and prepared from a pomegranate, purple carrot, and eggplant peel. The absorbance spectra was measured in the wavelength range 300-800 nm. The linear properties measurements of the prepared natural dye freestanding films were determined include absorption coefficient (α0), extinction coefficient (κ), and linear refraction index (n). The nonlinear refractive index n2 and nonlinear absorption coefficient β2 of the natural dyes in the water solution were measured by the optical z-scan technique under a pumped solid state laser at a laser wavelength of 532 nm. The results indicated that the pomegranate dye can be promising candidates for optical limiting applications with significantly low optical limiting of 3.5 mW.